Effect of running wheel as environmental enrichment for Balb/c mice on anxiolytic-type behavior - Paraguassú, Thalita Moreira; Cunha, Guilherme Nascimento (Disciplinarum Scientia | Saúde, 2024)
Since ancient times, the animals have been used to advance scientific development. However, the management of these animals might trigger unwanted behavioral and physiological changes. Therefore, there has been a lot of discussion about the environmental enrichment. In this context, this study aims to evaluate the effects of the running wheel on the anxiolytic-type behavior in Balb/c mice. Thirty mice were used, distributed in 2 groups, Control and Enriched Group, with 15 animals each. In the beginning of the research, the animals were fasted for 12 hours and the glucose measurement and weighing were performed. After that, the animals were kept in mini-insulators for 30 days and the fasting, the measurement and weighing procedures were performed again. After 24 hours, the Open Field test and the Elevated Plus Maze test were performed. The statistic analysis Shapiro-Wilk, Mann-Whitney and Wilcoxon, Student-newman-keuls were performed. When evaluating glucose and body weight, a decrease in values was noted in the Enriched Group (p<0.05). In the Elevated Plus Maze test, a longer period of time spent in the open arm was also observed (p<0.05) in this group. There was no statistical difference in the number of entries (p>0.05). In the Open Field, a longer center time and a greater number of rearings (p<0.05) were found in the Enriched Group. Regarding the distance traveled, there was statistical difference (p<0.0001), however, defecations and groomings there was no difference (p>0.05). It is concluded that the running wheel showed positive results in blood glucose levels and body weight. In addition, the stress caused by housing was minimized through environmental enrichment.